Employee OrganÄ±zatÄ±onal CommÄ±tment and Its Effect On Turnover IntentÄ±on BehavÄ±or In MultÄ±-FÄ±nance Industry - Rumawas, Wehelmina (APMBA (Asia Pacific Management and Business Application), 2021)
One of the indicator of successful organization that boost HR practices is that they can retain employees. Therefore companies are encouraged to take action to reduce turnover as one of the popular HR program that could retain employees. This study aims to examine the impact of multi-finance employee organizational commitment on turnover intention behaviour. Survey within the finance sector business and disributing questionnaire was used to obtain data from 212 respondents from 30 multi-finance companies. The data were analyzed through the PLS-SEM model using smartPLS-3 software. The results show that organizational commitment has a positive and significant effect on attitude toward leaving, subjective norm, and perceived behavioural control; thus, it impacts employee turnover intention. The significant indirect impact of organizational commitment on turnover intention was also revealed. The model clearly expresses the organizational commitment of multi-finance employees and its impact on turnover intention through the theory of planned behaviour construct. Managers need to understand these factors and their impact on turnover intention.